Predictors of 30-day mortality among patients with stroke admitted at a tertiary teaching hospital in Northwestern Tanzania: A prospective cohort study - Matuja, Sarah Shali; Mlay, Gilbert; Kalokola, Fredrick; Ngoya, Patrick; Shindika, Jemima; Andrew, Lilian; Ngimbwa, Joshua; Ahmed, Rashid Ali; Tumaini, Basil; Khanbhai, Khuzeima; Mutagaywa, Reuben; Manji, Mohamed; et al. (Frontiers in Neurology, 2023)
Background: Stroke is the 2nd leading cause of death worldwide, with the highest mortality rates seen in Low-middle-income countries, particularly in sub-Saharan Africa. We aimed to investigate the predictors of 30-day mortality among stroke patients admitted at a tertiary teaching hospital in Northwestern Tanzania. Methods: This cohort study recruited patients with a World Health Organization clinical definition for stroke. Data were collected on baseline characteristics, degree of neurological impairment at admission (measured using the National Institutes of Health Stroke Scale), imaging and electrocardiogram (ECG) findings and post-stroke complications. The modified Rankin Scale (mRS) was used to assess stroke outcomes. Kaplan Meier analysis was used to describe survival and Cox-proportional hazards model was used to examine predictors of mortality. Results: A total of 135 patients were enrolled with a mean age of 64.5 years. Hypertension was observed in 76% and 20% were on regular anti-hypertensive medications. The overall 30-day mortality was 37%. Comparing patients with hemorrhagic and ischemic stroke, 25% experienced mortality by day-5 (25th percentile survival time (in-days): 5 (95% CI: 2-14) vs day-23 (25th percentile survival time (in days): 23 (95% CI: 11-30) (Log-rank p<0.001) respectively. Aspiration pneumonia was the leading medical complication, seen in 41.3%. ECG abnormalities were observed in 54.6% vs 46.9% of patients with hemorrhagic and ischemic stroke respectively. The most common patterns were: ST changes 29.6% vs 30.9%, T-wave inversion 34.1% vs 38.3% and U-waves 18.2% vs 1.2% in hemorrhagic and ischemic stroke respectively. Independent predictors for case mortality were: mRS score (4-5) aHR 5.50 (95% CI:2.02-15.04), aspiration pneumonia aHR 3.69 (95% CI:1.71-13.69), ECG abnormalities aHR 2.28 (95% CI:1.86-5.86) and baseline stroke severity aHR 1.09 (95% CI:1.02-1.17). Conclusions: Stroke is associated with a high 30-day mortality in Northwestern Tanzania. Concerted efforts are warranted in the prevention and management of stroke patients with special attention to individuals with severe strokes, ECG abnormalities, and swallowing difficulties in order to reduce early morbidity and mortality.